Analysis of patients with colorectal cancer and brain metastases. (November 2016) - Fukuda, Koji; Matsuoka, Yoshisuke; Ota, Ibuki; Seki, Hirobumi; Ito, Shukuei; Kato, Satoshi
Brain metastases from colorectal cancer (CRC) are relatively rare. However, the incidences of brain metastasis have increased. We investigated 516 CRC patients who developed recurrence or metastatic disease. We investigated the primary site, distant metastasis, histological type, clinical features of processes of death and neurological symptoms. Brain metastases were detected in 5.8%. Odds ratios were 6.89 for the lung metastasis (p < 0.001), 0.43 for the liver (p = 0.04). The survival after brain metastasis was significantly poor in multiple brain metastases (hazard ratio: 4.12; p = 0.03) and poor performance status (hazard ratio: 5.38; p = 0.003). Lung metastasis is a higher factor and liver metastasis is a lower factor of brain metastasis. Survival after brain metastasis was poor in multiple brain metastasis and poor performance status.